2022
DOI: 10.4103/ijmr.ijmr_1631_20
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of hepatitis A vaccines by income level of the country: A systematic review

Abstract: Background & objectives: Although several reviews of economic evaluation (EE) studies on hepatitis A virus (HAV) vaccine exist, there remains a need to corroborate such data from time to time. This study aimed to systematically review the literature for reports on EE of HAV vaccination by type of population, characteristics of intervention and income level of the country. Methods: PubMed and Scopus were searched to identify relevant studies from inception up to May 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…It was highlighted that our results were similar to those of studies conducted in middle-income countries including countries in Asia region, which indicating that hepatitis A vaccination among children were likely to be cost-effective or even cost-saving [ 18 , 20 , 21 , 48 ]. The reason that our results was in line with the studies conducted in middle income countries including China and Indonesia is probably due to similar context related to endemicity of hepatitis A.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It was highlighted that our results were similar to those of studies conducted in middle-income countries including countries in Asia region, which indicating that hepatitis A vaccination among children were likely to be cost-effective or even cost-saving [ 18 , 20 , 21 , 48 ]. The reason that our results was in line with the studies conducted in middle income countries including China and Indonesia is probably due to similar context related to endemicity of hepatitis A.…”
Section: Discussionsupporting
confidence: 86%
“…With improvement in living and economic condition over the past decades, HAV infection is shifting from early childhood to adolescence and young adulthood reflecting epidemiological transition of hepatitis A in Kerala state, India [ 9 , 49 ] resulting in an increased risk of getting hepatitis A infection [ 11 , 50 ]. Previous studies [ 48 , 51 ] as well as a recent systematic review [ 21 ] on economic evaluation of hepatitis A vaccination suggested that incidence of hepatitis A is one of the most influential factors in the cost-effectiveness of hepatitis A vaccination. In addition, our results were consistent with the WHO recommendations that vaccination against hepatitis A be integrated into the national immunization schedule for children aged ≥ 1 year on the basis of incidence of hepatitis A, change in endemicity from high to intermediate, and considering the cost-effectiveness of vaccination strategy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation